Monetary Policy and Asset Prices: To Respond or Not? - Q. Farooq Akram; Gunnar Bardsen; Øyvind Eitrheim (Norges Bank, 2005)
We investigate whether there is a case for asset prices in interest rates rules within a small econometric model of the Norwegian economy, modeling the interdependence of the real economy, credit and three classes of assets prices: housing prices, equity prices and the nominal exchange rate. We compare the performance of simple and efficient interest rate rules that allow for response to movements in asset prices to the performance of more standard monetary policy rules. We find that including housing prices and equity prices in the policy rules can improve macroeconomic performance in terms of both nominal and real economic stability. In contrast, a response to nominal exchange rate fluctuations can induce excess volatility in general and prove detrimental to macroeconomic stability.
hdl:11250/2498436
Keywords: C51; C52; C53; E47; E52; 330; monetary policy; asset prices; simple interest rate rules; econometric model